Engaging Preservice Teachers in Context-based, Action-oriented Curriculum Development. Issue 3 (23rd March 2016) - Richards, K. Andrew R.; Ressler, James D.
Abstract : Physical education teacher education programs have a responsibility to prepare students in the technical aspects of teaching physical education, while also helping them to develop an awareness of the micropolitical cultures of schools that have implications for the implementation of what has been learned. Without the latter, beginning teachers may experience reality shock when transitioning into school contexts that do not align with the messages instilled during teacher education. Drawing upon lessons learned through research related to occupational socialization theory, the purpose of this article is to present a formative, context-based approach to curriculum development linked to project-based learning. The project is broken into seven steps that build upon one another and span the entire academic semester. Students work closely with cooperating teachers to develop units of instruction that utilize innovative curricular approaches and can be implemented in the teachers' contexts. Strategies for assessment are discussed, as are implications of the project more generally.